Mitigation of subway-induced low-frequency vibrations using a wave impeding block. (November 2022) - Chen, Juan; Geng, Jianlong; Gao, Guangyun; Luo, Wei; Liu, Yazhen; Li, Kejin
Abstract: The effective control of low-frequency vibrations induced by subway operation remains a problem, but wave impeding blocks (WIBs) have the potential to solve this issue. To investigate the vibration isolation behavior of WIB under subway loading, this study established a coupled track-tunnel-ground-WIB model using the two-and-a-half dimensional finite element method (2.5D FE). The effect of bedrock on wave propagation was first revealed by analyzing the eigenfrequencies of the soil layer with a tunnel. It was found that the bedrock reduced ground-borne vibrations with a frequency lower than the cut-off frequency of the soil layer. Based on this observation, the vibration isolation behavior of the WIB with different locations, embedding depths, material types, and dimension parameters was analyzed in detail. The WIB located beneath the tunnel invert (near-field active vibration isolation) exhibits a completely different behavior than that beneath the ground surface (far-field passive vibration isolation). The former can reduce ground vibrations in the entire ground surface, whereas the latter only works in a limited region directly above the WIB. The far-field vibration isolation effect is not sensitive to the vibration frequency and embedding depth, but the WIB dimension and rigidity have a significant impact. The near-field vibration isolation effect is most significantly influenced by the embedding depth, followed by the material property and dimension parameter. The WIB installed beneath the tunnel invert with a thinner embedding depth and stiffer rigidity more effectively isolates low-frequency vibrations induced by the subway.